Studies on Physiological Maturity in Phyllanthus amarus Schum and Thonn - SANTHOSH S,; HIPPARAGI,; D.M. VENKATA REDDY,; RAME GOWDA,; K. VISHWANATH, (Seed Research, 2026)
The field and laboratory studies on maturity in Phyllanthus amarus were carried out at the Gandhi Krishi Vignana Kendra, University of Agricultural Sciences, Bangalore during rabi 2002. The results of the study indicated that the seeds of Phyllanthus amarus attained maximum dry weight (136g) at 53-55 days after anthesis (DAA). At this stage fruits turned to brown colour with moisture content of around 27.65 per cent and seed germination (88%) and vigour index (625) were also found to be highest indicating crop attained physiological maturity. For seed purpose under Bangalore condition the Phyllanthus amarus needs to be harvested around 55 days after anthesis.